The standards developed by the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment - Birtles, Alexander Doyle (2001)
This thesis aims to examine a selection of the standards identifiable in the published work of the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment ("the CPT"). Part I commences with an examination of the mandate and modus operandi of the Committee, followed by an exposition of the two fundamental principles - of confidentiality and co-operation - which inform its work. The CPT's standard-setting work is introduced by means of an examination of its evolution and rationale, the purport of standards set and the ways in which such standards find expression.